Keanekaragaman Jenis Vegetasi Hutan Rawa Gambut di Hutan Desa Hiyang Bana, Kabupaten Katingan, Propinsi Kalimantan Tengah: Diversity of Peat Swamp Forest Vegetation Types in The Hiyang Bana Village Forest, Katingan District, Central Kalimantan Province - Cakra Birawa; Antonius Triyadi; Lies Indrayanti; Nisfiatul Hidayat; Anggelina Hoar (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
This study was conducted to determine the diversity of vegetation species in the Hiyang Bana Village Forest, a lowland peat swamp area that has important ecological functions but is under pressure from illegal logging and illegal gold mining activities. This pressure is feared to cause changes in the composition and structure of vegetation and reduce the ability of natural regeneration. This study aims to identify the types of vegetation and determine the diversity of vegetation species in the Hiyang Bana Village Forest. The method used was a combination of grid lines on 2 (two) research routes with a total of 26 sample plots. The results showed that there were 29 types of vegetation from 22 families, with different species dominating at each growth stage, such as punak at the seedling and pole levels, sand-sand at the stakes, and gemor at the trees. The value of species diversity ranged from low to moderate, with the highest value at the pole level (H’ = 2.60). The evenness index (E = 0.77) included the highest evenness. The species richness index (R = 5.15) including at the sapling growth stage had a high species richness value. These results indicate that the vegetation structure remains relatively stable, although anthropogenic pressures have the potential to inhibit natural regeneration. This research underscores the importance of sustainable management and rehabilitation efforts to maintain the sustainability of the Hiyang Bana Village Forest.